Enlarged temporal integration window in schizophrenia indicated by the double-flash illusion - Haß, Katharina; Sinke, Christopher; Reese, Tanya; Roy, Mandy; Wiswede, Daniel; Dillo, Wolfgang; Oranje, Bob; Szycik, Gregor R. (Cognitive neuropsychiatry, 2017)
Introduction: In the present study we were interested in the processing of audio-visual integration in schizophrenia compared to healthy controls. The amount of sound-induced double-flash illusions served as an indicator of audio-visual integration. We expected an altered integration as well as a different window of temporal integration for patients. Methods: Fifteen schizophrenia patients and 15 healthy volunteers matched for age and gender were included in this study. We used stimuli with eight different temporal delays (stimulus onset asynchronys (SOAs) 25, 50, 75, 100, 125, 150, 200 and 300 ms) to induce a double-flash illusion. Group differences and the widths of temporal integration windows were calculated on percentages of reported double-flash illusions. Results: Patients showed significantly more illusions (ca. 36-44% vs. 9-16% in control subjects) for SOAs 150-300. The temporal integration window for control participants went from SOAs 25 to 200 whereas for patients integration was found across all included temporal delays. We found no significant relationship between the amount of illusions and either illness severity, chlorpromazine equivalent doses or duration of illness in patients. Conclusions: Our results are interpreted in favour of an enlarged temporal integration window for audio-visual stimuli in schizophrenia patients, which is consistent with previous research.